Designing a compatibilized TPU/PE-G-MA/PP Blend for next generation 3D printed filament - Sohif, Hajar Naemah; Manshor, Hanisah; Mohd Hatta, Maziati Akmal; Sahab, Mohd Shaiful (Kulliyyah of Engineering International Islamic University Malaysia (IIUM) 53100 Gombak, Selangor, Malaysia, 2025)
This study addresses the incompatibility of thermoplastic polyurethane (TPU) and polypropylene (PP) to generate reusable, 3D-printed medical devices, reducing single-use plastic waste. TPU/PP blends were melt-mixed at different ratios (90/10, 80/20, 70/30) with a compatibilizer, polyethylene-graft-maleic anhydride (PE-g-MA), 1-5 wt%. Scanning Electron Microscopy (SEM) revealed that uncompatibilized blends had poorly dispersed TPU particles in the PP matrix. Adding PE-g-MA significantly improved blend homogeneity, reducing phase separation. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed enhanced compatibility, evidenced by an increased ester carbonyl (C=O) peak near 1735 cm⁻¹ and a decrease in anhydride groups. The most optimal formulation is the TPU30/PP70 blend with 3 wt% PE-g-MA. This research demonstrates that PE-g-MA successfully compatibilizes immiscible TPU/PP blends. These findings enable the development of advanced, sterilizable materials for fused deposition modeling (FDM) 3D printing in healthcare, promoting sustainability through reusable medical tools.